Boserupian pressure and agricultural mechanization in modern Ghana - Cossar, Frances (International Food Policy Research Institute, 2016)
The adoption of machinery in agricultural production in Africa south of the Sahara has been far behind the level of mechanization found in Asia and Latin America. However, recent survey data have revealed high levels of machinery use in localized areas of cereal production in northern Ghana. A survey conducted by the International Food Policy Research Institute, in partnership with the Savannah Agriculture Research Institute, found that in some areas more than 80 percent of farmers were using machinery for at least one operation. This paper considers the theoretical drivers of agricultural intensification, as outlined by Boserup, Pingali, and Binswanger, and the extent to which they are able to explain the spatial variation in machinery use found in northern Ghana. Population pressure, market access, and agroecological conditions are considered key drivers that cause farmers to find ways to increase productivity and adopt new technologies. Combining survey data with geospatial datasets, the empirical analysis finds that population growth and travel time to the local urban center explain a significant and large proportion of the variation in machinery use by farmers.